Modernisasi Pendidikan Pondok Pesantren Buq’ah Mubarokah, Pahesan, Godong, Grobogan - Lestari, Indah; Muhammad Amali El ‘Ubbad; Muhammad Cholil (Redtech Putra Benua, 2024)
Islamic boarding schools are educational institutions that have long roots in Indonesian culture. Islamic boarding schools have been around for hundreds of years, and have reached almost all levels of Muslim society. It developed with unique institutions over the centuries as an Islamic educational institution that was independent and free from the influence of Western-European colonial education. However, in line with developments over time, most Islamic boarding schools have made various improvements and improvements as an effort to modernize the education they provide. The modernization of the Islamic boarding school education system is always evolving, developing slowly towards continuous improvement. These changes are sought by keeping up with the times along with the unstoppable demands of the situation. This can be seen from the Islamic boarding school education system which was transformed into a madrasa. However, in line with developments over time, most Islamic boarding schools have made various improvements and improvements as an effort to modernize the education they provide. From traditional methods to classical systems, from halaqah systems to tiered systems, from traditional curricula to modern curricula, from classical education to educational reform, to aspects of management. In the midst of regional and global competition, efforts are being made to modernize the Islamic boarding school education system to maintain its existence as an educational institution that maintains national identity, in addition to paying attention to an educational identity based on science and Islamic values.